Expression of the UVR8 photoreceptor in different tissues reveals tissue‐autonomous features of UV‐B signalling. (27th March 2017) - Bernula, Péter; Crocco, Carlos Daniel; Arongaus, Adriana Beatriz; Ulm, Roman; Nagy, Ferenc; Viczián, András
Abstract: The Arabidopsis UV‐B photoreceptor UV RESISTANCE LOCUS 8 (UVR8) orchestrates the expression of hundreds of genes, many of which can be associated with UV‐B tolerance. UV‐B does not efficiently penetrate into tissues, yet UV‐B regulates complex growth and developmental responses. To unravel to what extent and how UVR8 located in different tissues contributes to UV‐B‐induced responses, we expressed UVR8 fused to the YELLOW FLUORESCENT PROTEIN (YFP) under the control of tissue‐specific promoters in a uvr8 null mutant background. We show that (1) UVR8 localized in the epidermis plays a major role in regulating cotyledon expansion, and (2) expression of UVR8 in the mesophyll is important to protect adult plants from the damaging effects of UV‐B. We found that UV‐B induces transcription of selected genes, including the key transcriptional regulator ELONGATED HYPOCOTYL 5 ( HY5 ), only in tissues that express UVR8. Thus, we suggest that tissue‐autonomous and simultaneous UVR8 signalling in different tissues mediates, at least partly, developmental and defence responses to UV‐B. Summary Statement: This work analyses how the UV‐B specific photoreceptor UVR8 regulates signalling, development and growth when expressed only in specific tissues. We show that early steps of UVR8‐dependent signalling, such as accumulation of the key regulatory transcription factor HY5, occur strictly in tissue‐autonomous fashion. In contrast, complex UV‐B‐induced changes, including proper acclimation of adult plants requires simultaneous signalling in the epidermal and mesophyll cells and/or inter‐tissue signalling.